Complementary Support from Facilitators and Peers for Promoting mHealth Engagement and Weight Loss. Issue 11 (2nd November 2017) - Kim, Heewon; Ray, Colter D.; Veluscek, Alaina M.
Abstract : This study investigates the effects of mHealth interventions on sustainable behavior change and weight loss, drawing on in-app user activity data and online survey data. Specifically, we focus on the interactions within mobile support groups in Noom, an mHealth application for obesity intervention, to delve into how social support from facilitators and peers may play differential roles in promoting health outcomes. The results of structural equation modeling ( N  = 301) demonstrated that (a) perceived facilitator support was positively associated with group members' health information acquisition such as fitness-themed article reading whereas perceived peer support was positively linked to group participation such as posting and responding; (b) perceived peer support was positively related to normative influence among group members, which subsequently increased group members' responses to others' posts; and (c) health information reading and in-group posting promoted weight loss; however, merely responding to others' posts did not lead to weight-loss success. The findings suggest that the complementary influences of facilitators and peers must be considered to enhance the efficacy of support group interventions.